A Novel Mixed Methods Approach Combining Geospatial Mapping and Qualitative Inquiry to Identify Multilevel Policy Targets: The Focused Rapid Assessment Process (fRAP) Applied to Cancer Survivorship. (April 2022) - Kieber-Emmons, Autumn M.; Miller, William L.; Rubinstein, Ellen B.; Howard, Jenna; Tsui, Jennifer; Rankin, Jennifer L.; Crabtree, Benjamin F.
Multilevel perspectives across communities, medical systems and policy environments are needed, but few methods are available for health services researchers with limited resources. We developed a mixed methods health policy approach, the focused Rapid Assessment Process (fRAP), that is designed to uncover multilevel modifiable barriers and facilitators contributing to public health issues. We illustrate with a study applying fRAP to the issue of cancer survivorship care. Through this multilevel investigation we identified two major modifiable areas affecting high-quality cancer survivorship care: (1) the importance of cancer survivorship guidelines/data and (2) the need for improved oncology–primary care relationships. This article contributes to the mixed methods literature by coupling geospatial mapping to qualitative rapid assessment to efficiently identify policy change targets.